2017
DOI: 10.1038/srep42957
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer Cell Mitochondria Targeting by Pancratistatin Analogs is Dependent on Functional Complex II and III

Abstract: Enhanced mitochondrial stability and decreased dependence on oxidative phosphorylation confer an acquired resistance to apoptosis in cancer cells, but may present opportunities for therapeutic intervention. The compound pancratistatin (PST) has been shown to selectively induce apoptosis in cancer cells. However, its low availability in nature has hindered its clinical advancement. We synthesized PST analogs and a medium-throughput screen was completed. Analogs SVTH-7, -6, and -5 demonstrated potent anti-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…A new class of compounds, collectively known as mitocans, includes anticancer agents that directly or indirectly target cancer cell mitochondria to selectively induce apoptosis (8). On the basis of our previous work, we classify SVTH-6 as such (24). Likewise, this study has shown SVTH-6 to selectively dissipate MMP in cancer cells, decrease oxygen consumption, and cause release of apoptogenic factors cytochrome c and AIF from isolated cancer cell mitochondria alone and in combination with a molecule that induces increased oxidative stress, PL (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new class of compounds, collectively known as mitocans, includes anticancer agents that directly or indirectly target cancer cell mitochondria to selectively induce apoptosis (8). On the basis of our previous work, we classify SVTH-6 as such (24). Likewise, this study has shown SVTH-6 to selectively dissipate MMP in cancer cells, decrease oxygen consumption, and cause release of apoptogenic factors cytochrome c and AIF from isolated cancer cell mitochondria alone and in combination with a molecule that induces increased oxidative stress, PL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The natural compound PL has previously been demonstrated to preferentially cause cytotoxicity in cancer cells by selectively targeting their stress response mechanisms against ROS (25). We wanted to investigate if PL is capable of enhancing the effect of SVTH-6 in cancer cells because we have previously shown SVTH-6 to be targeting cancer cell mitochondria (24). Interestingly, an enhanced cytotoxic effect was selectively produced with this combination treatment in cancer cells, including BxPC-3 pancreatic cancer, OVCAR-3 ovarian cancer, NCI-H23 nonsmall-cell lung cancer, MV-4-11 leukemia, and G-361 melanoma cells ( Fig.…”
Section: Selective Induction Of Cytotoxicity In Cancer Cells By Svth-mentioning
confidence: 99%
See 1 more Smart Citation
“…3 For example, pancratistatin ( 1 ) showed substantial in vivo activity against murine P-388 lymphocytic leukemia and murine M-5076 ovary sarcoma, and reduced growth of subcutaneous colon HT-29 tumors. 4 Moreover, experiments examining pancratistatin-induced apoptosis revealed noticeably reduced death in noncancerous cells relative to cancer cell lines, making these compounds appealing clinical lead candidates. 5 Finally, pancratistatins also showed significant antiviral activities, including in vivo models for Japanese encephalitis, 6 a disease for which no other known small-molecule anti-infective agent exists.…”
mentioning
confidence: 99%
“…To this end, deprotection of urazole 12 to free amine 14 using conditions to affect hydrolysis and N–N bond cleavage proved challenging, as aggressively acidic or basic conditions led to complete decomposition of starting material. Therefore, we explored hydride-based reducing agents and found that treatment of 12 with LiAlH 4 could reduce the urazole; however, the resulting cyclic hydrazine hemiaminal 13 proved unstable, complicating its isolation and the overall reproducibility of this step. To overcome this hurdle, we decided to developed a one-pot protocol that directly reduced urazole 12 to amine 14 without handling the sensitive intermediate 13 .…”
mentioning
confidence: 99%